Possible mechanisms underlying the association between human T-cell leukemia virus type 1 (HTLV-1) and hypertension in elderly Japanese population - Yuji Shimizu; Kazuhiko Arima; Yuko Noguchi; Shin-Ya Kawashiri; Hirotomo Yamanashi; Mami Tamai; Yasuhiro Nagata; Takahiro Maeda (Komiyama Printing Co. Ltd, 2021)
Abstract Background Human T-cell leukemia virus type 1 (HTLV-1) activates inflammatory cascades by activating the NF-κB pathway. The minor allele of single nucleotide polymorphism (SNP) in breast cancer suppressor BRCA1-associated protein (BRAP), which has a common etiology with HTLV-1 infection, has been reported to be positively associated with carotid atherosclerosis, but inversely associated with hypertension. Therefore, HTLV-1 infection may be inversely associated with hypertension by activating endothelial maintenance, including atherosclerosis. To clarify these associations, a cross-sectional study was conducted using 2989 Japanese individuals aged 60-99 years participating in a general health check-up. Methods Logistic regression models were used to clarify the association between HTLV-1 and hypertension. Platelet levels stratified analyses were also performed since platelet production, which plays a crucial role in endothelium maintenance, can be stimulated by activating the NF-κB pathway. Results HTLV-1 infection was found to be significantly inversely associated with hypertension, particularly in subjects with high platelet levels (≥ second tertiles of platelet levels); the fully adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were 0.75 (0.62, 0.92) for total and 0.64 (0.50, 0.82) for high platelet levels, respectively. Further analysis of the non-hypertensive subjects demonstrated that HTLV-1 infection was significantly positively associated with atherosclerosis in subjects with the highest tertile of platelet levels (2.11 [1.15, 3.86]) but not in subjects with low platelet levels (first and second tertiles of platelet level) (0.89 [0.57, 1.39]). Conclusion Asymptomatic HTLV-1 infection is inversely associated with hypertension, possibly by activating endothelial maintenance, including atherosclerosis progression.